2020
DOI: 10.3389/fmicb.2020.01603
|View full text |Cite
|
Sign up to set email alerts
|

HIV-2-Infected Macrophages Produce and Accumulate Poorly Infectious Viral Particles

Abstract: A significant proportion of HIV-2-infected patients exhibit natural virological control that is generally absent from HIV-1-infected patients. Along with CD4 + T cells, HIV-1 targets macrophages which may contribute to viral spreading and the latent reservoir. We have studied the relationship between macrophages and HIV-2, focusing on post-entry steps. HIV-2-infected monocyte-derived macrophages (MDMs) produced substantial amounts of viral particles that were largely harbored intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Alternatively, the lack of viral detection in supernatants of exposed cells may reflect a low-level viral replication in Mø and DCs. This lower viral replication is certainly strain-dependent and could be the result of the production of poorly infectious viral particles that accumulate in intracellular structures called virus-containing compartments (VCCs) [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the lack of viral detection in supernatants of exposed cells may reflect a low-level viral replication in Mø and DCs. This lower viral replication is certainly strain-dependent and could be the result of the production of poorly infectious viral particles that accumulate in intracellular structures called virus-containing compartments (VCCs) [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIV-2-infected and HIV-1-infected cells show different metabolic profiles by vpx-mediated SAMHD1 degradation [41]. Another difference between HIV types is that HIV-2 infected macrophages produce poorly infectious HIV particles and they may as such contribute to immune control of HIV-2 [42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found evidence that LAPTM5 can target HIV-2 and the primate lentiviruses SIV mac239 and SIV agm but not MLV and FIV to restrict host infection, raising the possibility that LAPTM5 has a broader role in innate antiviral immunity against primate lentiviruses. Interestingly, HIV-2 infectivity was shown to be much lower than that of HIV-1 when the virus was produced in MDMs 37 , and Gea-Mallorquí et al recently reported that HIV-2 infection of macrophages produces and accumulates poorly infectious viral particles 38 . It is likely that the presence of LAPTM5 is partly responsible for the poorly infectious HIV-2 virions produced in macrophages, given that Vpr of HIV-2 cannot promote degradation of human LAPTM5.…”
Section: Discussionmentioning
confidence: 99%